Quantitative analysis of observed signatures in phonon reflection experiment - Li, Jin (Journal of physics. Condensed matter, 2020)
For phonons propagating in a crystal at low temperature, we develop a phonon reflection model and an analysis framework to fully understand reflection peaks from underlying physics principles. Our study shows that the specular reflection structure of peaks contains detailed information about properties of the crystal material, and provides a solid quantitative link between phonon theory and experimental signals. For both kinds of experiments that either use crystal as a particle detector or as a target material for study, this analysis provides a novel and essential method to understand the experimental signatures.